Irritable bowel syndrome concept from the gut microbiom point of view - Anna F. Sheptulina; Vladimir T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of review. To present data on integration of nutritional pattern and intestinal microbiom spectrum, to estimate the role of each of the listed factors in development of irritable bowel syndrome (IBS) symp toms. Summary. In spite of the fact, that IBS is one of the most common gastrointestinal functional disease, etiol ogy of disease is substantially unknown. Among factors which promote IBS development specific features of the patient and environmental factors, first of all nutritional stereotype and dietary pattern are considered nowa days. These in turn exert direct impact on quantitative and qualitative spectrum of gastrointestinal microbiota which changes, as it was demonstrated in the recent original studies, is an integral part of IBS pathogenesis and is the cornerstone of symptom origin of this func tional disorder. Conclusion. Pattern of intestinal microbiome, nutrition al stereotype and dietary pattern should be taken into account at management of IBS and planning of clinical or pilot studies in this area.